2003
DOI: 10.1021/tx0341714
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Speciation in Urine from Acute Promyelocytic Leukemia Patients undergoing Arsenic Trioxide Treatment

Abstract: Arsenic has been used successfully in clinical trials for treating acute promyelocytic leukemia (APL). Although sublethal doses of inorganic arsenic are used, little is known about the pharmacokinetics and metabolism of the high levels of arsenic in APL patients. To fill this important gap, this study describes the speciation of arsenic in urine from four APL patients treated with arsenic. Each patient was injected daily with an arsenite (As(III)) solution that contained 10 mg of As(2)O(3) precursor. Speciatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
94
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(101 citation statements)
references
References 50 publications
5
94
1
1
Order By: Relevance
“…Although the pentavalent forms of monomethylarsonate and dimethylarsinate seem more readily excreted than inorganic arsenic, several studies have shown that MMA3 is more acutely toxic than dimethylarsinate or inorganic arsenic (25)(26)(27)(28)(29)(30)(31)(32). Only a few studies have investigated the presence of MMA3 in nonchelated humans (45,57,58). In a study of six subjects from an arsenic-exposed region in Mexico, the proportion of urinary MMA3 was 0.9%, whereas the proportions of inorganic arsenic, MMA5, DMA3, and DMA5 were 23.5%, 18.5%, 8.8%, 48.2%, respectively (45).…”
Section: Discussionmentioning
confidence: 99%
“…Although the pentavalent forms of monomethylarsonate and dimethylarsinate seem more readily excreted than inorganic arsenic, several studies have shown that MMA3 is more acutely toxic than dimethylarsinate or inorganic arsenic (25)(26)(27)(28)(29)(30)(31)(32). Only a few studies have investigated the presence of MMA3 in nonchelated humans (45,57,58). In a study of six subjects from an arsenic-exposed region in Mexico, the proportion of urinary MMA3 was 0.9%, whereas the proportions of inorganic arsenic, MMA5, DMA3, and DMA5 were 23.5%, 18.5%, 8.8%, 48.2%, respectively (45).…”
Section: Discussionmentioning
confidence: 99%
“…These observations together with our recent study [31] suggest that biomethylation may in fact generate potentially cytocidal metabolites that may significantly contribute to the therapeutic effect as well as side effects of ATO in APL patients. Indeed, MAs III and DMAs III have been detected in the urine of APL patients undergoing ATO treatment [167] and healthy individuals who have drunk water containing inorganic arsenic [155,168], and in human hepatoma (HepG2) cells exposed to As III [155]. Therefore, elucidation of arsenic metabolism is very important for achieving better therapeutic effects, and is critical in reducing side effects of ATO.…”
Section: Metabolism and Pharmacokineticsmentioning
confidence: 99%
“…25 Measurements of ATO metabolites in urine have led to differing results across several studies, ranging from 1-8 to 19% or 32À65%. [24][25][26][27] Independently of this unexplained broad range, the results indicate that other elimination mechanisms, such as bile and feces, must have a role in the excretion of high arsenic doses. In a study of adult cancer patients with varying degrees of renal dysfunction, systemic exposure of arsenic and its methylated metabolites following standard dosing of ATO was increased.…”
Section: Pharmacokineticsmentioning
confidence: 97%